Pemetaan Lokasi Rumah Kos di Daerah Universitas Brawijaya Kota Malang dengan Sistem Informasi Geografis (SIG) - pratama, iqbal annur nugraha (Jurnal Vokasi Teknik Sipil, 2023)
The increasing number of new students in Malang City each year has led to an increase in the demand for student necessities such as boarding houses, accommodations, food, transportation, and daily necessities. Boarding houses are considered one of the essential needs for new students as they provide a place to stay during their college education. This research aims to determine the mapping results and distribution patterns of boarding houses located in the area of Brawijaya University, Malang City, using ArcGIS software. Geographic Information System (GIS) is a computer-based information system that combines geographic maps and related information. The nearest neighbor analysis (NNA) is employed in this study to explain the distribution pattern of boarding houses by considering distance, the number of locations, and the area's size. The researcher conducted the analysis using two methods: manual calculation and ArcGIS 10.3 software. The analysis resulted in a distribution pattern with clustering categories in the areas of Ketawanggede and Penanggungan sub-districts in Malang City, with a T-value of 0.630 for both calculation methods.